2009
DOI: 10.1186/2047-783x-14-10-447
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of limb alignment measurement for high tibial osteotomy with a navigation system

Abstract: ObjectiveHigh tibial osteotomy (HTO) is one treatment option for young and active patients with unicompartmental osteoarthritis. The success of this procedure substantially depends on the degree of correction of the mechanical axis. Computer-assisted navigation systems are believed to improve the precision of axis correction through intraoperative real-time monitoring. This study investigates the accuracy of limb alignment measurements with a navigation system on a cadaver specimen.Materials and methodsThe mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
(20 reference statements)
0
20
0
4
Order By: Relevance
“…The navigation system has been used in tibial osteotomies for almost a decade and provides information about the alignment, the load axis, varus and valgus stress, speed, range of motion, limb length and slope. Despite the increased surgical time and the fact that it has a longer learning curve, navigation is considered a promising adjunct for intraoperative use to avoid under-and overcorrections [7,[11][12][13][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The navigation system has been used in tibial osteotomies for almost a decade and provides information about the alignment, the load axis, varus and valgus stress, speed, range of motion, limb length and slope. Despite the increased surgical time and the fact that it has a longer learning curve, navigation is considered a promising adjunct for intraoperative use to avoid under-and overcorrections [7,[11][12][13][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several authors have described superior intraoperative accuracy using navigation systems for HTO. 15,16 In this feasibility study, we describe a new intraoperative three-dimensional (3D) positioning technique for calculating the location and dimensions of an opening wedge HTO and for surgically reproducing the planned osteotomy with safety and efficacy in a reduced surgical time.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, navigation alone does not affect operating time in any meaningful manner, as the Reising et al 27 study had an average time of 141 minutes between both groups, and Gebhard et al 18 documented average operating time of 105 minutes, with 60% of procedures completed within 60-120 minutes. For example, Akamatsu 25 demonstrated total operative time was significantly longer in the navigated group than in the conventional group (P < 0.001), whereas Hankemeier et al 23 demonstrated good inter-and intraobserver reliability 24 . Navigation is also unlikely to cause significant postoperative complications 24 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Akamatsu 25 demonstrated total operative time was significantly longer in the navigated group than in the conventional group (P < 0.001), whereas Hankemeier et al 23 demonstrated good inter-and intraobserver reliability 24 . Navigation is also unlikely to cause significant postoperative complications 24 . Clinically, however, there appears to be no advantage of navigation over conventional techniques 25,26 , a finding most probably attributable to inadequate follow-up data and insufficient sample sizes.…”
Section: Discussionmentioning
confidence: 99%